DIGITAL DIALOGIC READING IN CLIL PROGRAM FOR EFL MUSLIM PRIMARY SCHOOL LEARNERS - Khoiriyah, Khoiriyah; Farah, Rafika Rabba (JP (Jurnal Pendidikan) : Teori dan Praktik, 2024)
Dialogic reading has been valued by number of researchers to accellerate young learners’ literacy skills. This study aims to explore the implementation of dialogic reading method with Islamic content to students at Islamic primary school. Six-meeting teaching practices followed with a survey research was employed in this study. Results reveal that majority of students perceived positively toward the use of dialogic reading book with Islamic content as it enhances their engagement, comprehension, and vocabulary retention. Furthermore, their engagement and enjoyment are sourced in the dialogue undertaken between the teachers and students as well as the interactive quizziz given after each topic discussion. This study has shed a light that dialogic reading integrated with contextualized reading materials offers practitical strategies in fostering young learenrs’ literacy skills.